Assessment of Hygiene Status of Medical and Surgical Units Among Hospitals of Nowshera Swat & Peshawar Districts of Khyber Pakhtunkhwa Pakistan - Mehwish Saba Waheed, Naeemullah, Nadia Qazi, Bushra Ijaz, Zahid Khan, Nizam Muhammad Darwesh, Muhammad Ishtiaq (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Hygiene practices helps a lot in the prevention of infection among the admitted patients and an important component of infection prevention and patient safety. The aim of this study was to assess the hygiene status of medical and surgical units of selected hospitals in District Nowshera, Swat and Peshawar Districts, Pakistan. Material and Methods: It was a cross-sectional descriptive study, carried out in hospitals of Nowshera, Swat and Peshawar Districts, from August 2021 to February 2022. Data was collected from 60 medical and surgical units. A structured questionnaire was used to collect data, and face-to- face interviews were conducted with healthcare workers and patients. Finally results were presented in form of tables. Results: 64.66% of health care staff practice hand hygiene measures; and most of the surgeons (81.67%) were not satisfied with provided scrubbing materials. 46.67% of patients were satisfied with the prevailing hygiene status; 96.67% with health services. Moreover, 56.67% of patients wash hands before eating; 31.67% of sweepers satisfied with provision of materials, and surgical site infection rate was 13.33%. Furthermore, 63.33% of units collect waste daily; whereas only 18.33% had waste separation. 68.33% had isolation chamber for infectious cases; 36.67% screened patients for HIV/AIDS; and only 11.67% didn’t change fomites on daily basis. Conclusion: It was concluded that the hygiene status of selected hospitals was satisfactory. Moreover, the hygienic status showed strong relationship with type of unit; number of sweepers; waste collection frequency and frequency of fomites change and thus needs strategies to increase awareness and motivation of health care staff with an aim to reduce the incidence of hospital infections.